Investigation of the Relationship Between Cancer Patients' Perception of Nurse Presence and Psychological Resilience Levels. - DEMİR, Zahide Gül YAZGI; HAVLİOĞLU, Suzan; ÇELİK, Hanife; KARAAĞAÇ, Mustafa (Journal of Nursology, 2025)
Objective: In the literature, studies on how cancer patients perceive nurse presence and the effects of these perceptions on mental health are quite limited. In this study, it was aimed to determine the relationship between cancer patients' perception of nurse presence and psychological resilience levels. Methods: This descriptive study was conducted with 153 cancer patients hospitalised at the Turgut Özal Medical Centre Oncology Hospital in Malatya province. Data were collected using the Personal Information Form, Nurse Presence Scale and Adult Psychological Resilience Scale. Results: The mean score of the patients participating in the study was 89.31±19.93 on the Nurse Presence Scale and 98.31±22.11 on the Psychological Resilience Scale. No relationship was found between the mean scores of the Nurse Presence Scale and the Psychological Resilience Scale. It was determined that the level of cancer patients' perception of the presence of the nurse was above the medium level and their psychological resilience level was at the medium level. Conclusion: It is recommended to organize trainings to increase the awareness of nurses about offering their presence and to develop behaviors that enable them to offer their presence. In addition, evaluating the psychological resilience levels of patients at regular intervals and considering individual, environmental and cultural differences that may affect the psychological resilience level of patients may be effective in planning interventions to achieve positive results in the care to be provided.